Program â€œGerakan Subuh Mengajiâ€ Episode 152 â€œPendidikan Lingkungan Hidup Pada Anak Dan Remajaâ€ Di TVmu Dalam Menjalankan Fungsi Pendidikan - Nurul Hana Aprilia; Makroen Sanjaya (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Currently, only a small amount of local television in Indonesia is operating as a teaching medium due to a close rivalry amongst local broadcasters. According to current thinking, functions of menghiburlah are more prevalent in television media, thus there is only a small amount of local television that airs programs with educational goals. To understand how TVMu performs its function of education through the program "Gerakan Subuh Mengaji," specifically in Episode 152, "Pendidikan Lingkungan Hidup Pada Anak dan Remaja," the study in question uses the theory of mass communication and a perspective on the functions of mass communication, specifically those related to education. Utilizing qualitative research techniques, this study. Results of the study indicate that TVMu frequently broadcasts educational programming, such as ceramah or khotbah that is widely distributed. One example is from the program "Gerakan Subuh Mengaji," a daily LIVE YouTube broadcast that uses Zoom Meetings from 5:00 a.m. to 6:00 a.m.